Perioperative management of acute myocardial infarction in the 31st week of pregnancy: A case report and literature review - Sun, Pei; Liang, Xin-Quan; Hong, Tao; Zhang, Hong (Frontiers in Surgery, 2022)
Pregnancy-related acute myocardial infarction (PAMI) is rare but life-threatening. The incidence of PAMI is growing over time for multiple reasons, and the management of parturients with acute myocardial infarction is challenging in terms of diagnosis and treatment. To date, there are still no clear guidelines on the best practice for PAMI. We present a case of a 41-year-old woman with PAMI at 31 weeks of pregnancy. Through multidisciplinary collaboration, successful outcomes were achieved for both the mother and fetus.